Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/0020720920984000
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Research on the framework of intelligent classroom based on artificial intelligence

Abstract: The emergence of artificial intelligence has greatly improved the imbalance of resource allocation in different regions of China, and promoted education equity. Video is an important form of learning resources in the field of education. Educational video analysis and innovative application based on artificial intelligence technology greatly promote the innovation of education and teaching, and promote the deep integration of artificial intelligence and education. In this paper, firstly, the system architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In order to implement the entire process dynamic accompanying learning evaluation and assessment system in place, it is necessary to specifically determine each assessment item and quantify each assessment item [5]. The following is the assessment situation table of the entire process dynamic accompanying learning evaluation and assessment system, which provides detailed assessment items, weights, and requirements, as shown in Table 2.…”
Section: Quality Evaluation Indicators For Smart Classroomsmentioning
confidence: 99%
“…In order to implement the entire process dynamic accompanying learning evaluation and assessment system in place, it is necessary to specifically determine each assessment item and quantify each assessment item [5]. The following is the assessment situation table of the entire process dynamic accompanying learning evaluation and assessment system, which provides detailed assessment items, weights, and requirements, as shown in Table 2.…”
Section: Quality Evaluation Indicators For Smart Classroomsmentioning
confidence: 99%
“…Such education technologies could facilitate the content presentation, the management of the classroom, and the access to the learning resources; and they also implement the learning analytics and provide students with real-time feedback ( MacLeod et al, 2018 ). In the smart classroom, the instructors are more capable of providing their students with immediate feedback, and guiding, facilitating, monitoring, and assessing their students’ learning ( Li et al, 2021 ; Lu et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cai, Y. et al found that artificial intelligence technology can improve the recognition rate and accuracy of English learning software, which is of great significance for students' English learning [21]. Hu, Y. et al evaluated the effect of intelligent classrooms with artificial intelligence technology, and the results showed that the artificial intelligence technology classroom is more interactive and has better teaching effects compared with traditional classrooms [22]. Kim, N. et al analyzed the impact of AI on global education and emphasized the importance of AI technology to the future development of education [23].…”
Section: Introductionmentioning
confidence: 99%